2022
DOI: 10.5755/j02.mech.28195
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Conveying of Miniature and Microparts on a Platform Subjected to Sinusoidal Displacement Cycles with Controlled Dry Friction

Abstract: This paper presents a novel method for convey-ing of miniature and microparts on a subjected to sinusoi-dal displacement cycles in the horizontal direction when the effective coefficient of dry friction between the part and the platform is periodically being controlled. Hereby, the required dynamic directionality is achieved via the system asymmetry created by periodic alteration of the effective coefficient of dry friction between the micropart and the platform. A mathematical model of conveying process is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Recently, a method of bidirectional vibrational transportation was demonstrated that was achieved through an asymmetry created by dynamically controlling the frictional conditions between the object being manipulated and the platform subjected to harmonic (sinusoidal) oscillations along the horizontal direction [ 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a method of bidirectional vibrational transportation was demonstrated that was achieved through an asymmetry created by dynamically controlling the frictional conditions between the object being manipulated and the platform subjected to harmonic (sinusoidal) oscillations along the horizontal direction [ 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%